Influence of liquid assets and sectoral distribution of income on aggregate consumers behavior in Ireland - Kelleher, R. (Economic & Social Studies, 1977)
The purpose of this paper is to obtain a relationship that will explain movements in the ratio of consumers' expenditure to income. In recent years movements in this ratio have had important implications for the development of aggregate demand in the economy. A proper appreciation of the determinants of this ratio is a prerequisite for efficient stabilisation policy.
Keywords: Economics; Ireland